Dynamics of the chemical composition of rainwater throughout Hurricane Irene - K. M. Mullaugh; J. D. Willey; R. J. Kieber; R. N. Mead; G. B. Avery Jr. (Atmospheric Chemistry and Physics, 2013)
Sequential sampling of rainwater from Hurricane Irene was carried out in Wilmington, NC, USA on 26 and 27 August 2011. Eleven samples were analyzed for pH, major ions (Cl−, NO3−, SO42−, Na+, K+, Mg2+, Ca2+, NH4+), dissolved organic carbon (DOC) and hydrogen peroxide (H2O2). Hurricane Irene contributed 16% of the total rainwater and 18% of the total chloride wet deposition received in Wilmington NC during all of 2011. This work highlights the main physical factors influencing the chemical composition of tropical storm rainwater: wind speed, wind direction, back trajectory and vertical mixing, time of day and total rain volume. Samples collected early in the storm, when winds blew out of the east, contained dissolved components indicative of marine sources (salts from sea spray and low DOC). The sea-salt components in the samples had two maxima in concentration during the storm the first of which occurred before the volume of rain had sufficiently washed out sea salt from the atmosphere and the second when back trajectories showed large volumes of marine surface air were lifted. As the storm progressed and winds shifted to a westerly direction, the chemical composition of the rainwater became characteristic of terrestrial storms (high DOC and NH4+ and low sea salt). This work demonstrates that tropical storms are not only responsible for significant wet deposition of marine components to land, but terrestrial components can also become entrained in rainwater, which can then be delivered to coastal waters via wet deposition. This study also underscores why analysis of one composite sample can lead to an incomplete interpretation of the factors that influence the chemically divergent analytes in rainwater during extreme weather events.